Recent population changes of common waders and passerines in Iceland's largest lowland region - Pálsdóttir, Aldís Erna; Þórisson, Böðvar; Gunnarsson, Tómas G. (Bird study, 2025)
Iceland hosts several internationally important populations of ground-nesting birds in open habitats, particularly waders, but monitoring shows concerning declines among populations of several of these Icelandic land birds. To estimate population changes of ground-nesting birds in Iceland's largest lowland region from 2012 to 2024 and compare their densities to important landscape factors. Abundance of the nine most common species (seven waders and two passerines) in South Iceland was monitored with point counts in a roadside survey. Data on landscape factors were extracted from aerial photography and their relationships to bird densities were explored. Redwings Turdus iliacus increased over the period (∼12% annual increase), Common Snipes Gallinago gallinago did not show significant changes, but seven species declined by ∼2% to 10% annually (European Golden Plover Pluvialis apricaria, Eurasian Oystercatcher Haematopus ostralegus, Eurasian Whimbrel Numenius phaeopus, Black-tailed Godwit Limosa limosa, Dunlin Calidris alpina, Common Redshank Tringa totanus and Meadow Pipit Anthus pratensis). Densities of Eurasian Whimbrels and Dunlins increased with distance from permanent settlements while Common Snipe densities decreased, although the abundance change was unaffected. These rapid changes of open-habitat specialists in Iceland's largest lowland area are a grave cause for concern and call for a concerted effort to explore the drivers.